Families of plants most useful to man - Sears, Fred C. (My University, 1892)
Introduction: In any discussion as to the comparative value to man of the various families of plants, our estimate must be based on the nature of the wants which they supply and on the number and quality of the substitutes which are available in case they did not exist. Basing, then, our estimation of these things it is evident that those plants are most valuable which supply man with food, since a supply of food is one of the primary conditions for man’s existence. Anything else man may do without, if we except air and water, but cut of man’s food supply and he is of very little use. Looking at it in this way I consider that there is no family which has a better claim to the first place than Gramineae. It numbers among its representatives plants which grow in every country, temperate or tropical and the failure of the crop of a single representative may be sufficient to cause famine throughout an entire country. Wheat, Triticum vulgare, is probably the most universally used of any single plant food and when we consider the immense number of people with whom it is a staple article of diet, if not the staff of life; the quantity of it which is raised; and the number of people who make their whole, or at least a large part of their living by producing it for other people’s use, it might seem that this one species was sufficient to place this family in the front rank at least, if not at the very head.
Families of plants most valuable to man
Citation: Sears, Fred C. Families of plants most useful to man. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Gramineae; Grass; Plant; Botany; Edible; Theses; Manuscripts (documents)